Ketidakadilan Struktural dan Mobilisasi Buruh: Pemogokan Buruh Gula di Jawa, 1920 - ardiansyah, ardiansyah (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
The sugar workers’ strike in Java in 1920 was one of the most significant labor events in the history of colonial Indonesia, yet it has received relatively limited historiographical attention. Previous studies have often treated this episode as a subsidiary narrative within the broader rise of nationalism or the early development of the communist movement, leaving the underlying social and economic mechanisms insufficiently explored. This article argues that the 1920 strike emerged from the interaction between structural inequalities embedded in the colonial sugar industry and the process of collective mobilization carried out by labor organizations. Adopting a social historical approach with a descriptive-analytical method, this study combines historiographical secondary sources with primary materials from contemporary newspapers representing two different perspectives—Dutch-language colonial newspapers and Malay-language movement newspapers—as well as the labor movement text Penuntun Kaum Buruh written by Semaoen in 1920. The findings show that the strike was not a spontaneous response to a single triggering event, but rather the result of accumulated structural conditions such as wage stagnation, the proletarianization of rural labor, and the systematic refusal of union representation. These structural grievances were then articulated and mobilized through the activities of the Personeel Fabriek Bond, including propaganda meetings, networks of movement newspapers, and the publication of labor organizational texts. The 1920 strike can therefore be understood as the outcome of the convergence between structural tensions within the colonial sugar industry and the gradual formation of collective labor consciousness in Java.